Pengaruh Pembelajaran Berbasis Internet dan Konsep Diri Terhadap Hasil Peer Teaching - Etin Solihatin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
This aims of this research at improving result of peer teaching using Edmodo by reviewing self-concept. A quasi-experiment with 2x2 factorial design (two- way Anova) was employed in this study. Result of the study shows that (1) Result of peer teaching on groups of students using Edmodo is higher than that of using e-Mail. (2) There is an interaction between learning media and self-concept toward result of peer teaching. (3) Among groups of students having positive self-concept, result of peer teaching on the groups using Edmodo is higher than that of using e-Mail. (4) Among groups of students having negative self-concept, result of peer teaching on the groups using Edmodo is lower than that of using e-Mail.